Behavioral and Psychological Effects of Coronavirus Disease-19 Quarantine in Patients With Dementia - Cagnin, Annachiara; Di Lorenzo, Raffaele; Marra, Camillo; Bonanni, Laura; Cupidi, Chiara; Laganà, Valentina; Rubino, Elisa; Vacca, Alessandro; Provero, Paolo; Isella, Valeria; Vanacore, Nicola; Agosta, Federica; et al. (Frontiers in Psychiatry, 2020)
BACKGROUND: In March 2020, the World Health Organization declared a global pandemic due to the novel coronavirus SARS-CoV-2 and several governments planned a national quarantine in order to control the virus spread. Acute psychological effects of quarantine in frail elderly subjects with special needs, such as patients with dementia, have been poorly investigated. The aim of this study was to assess modifications of neuropsychiatric symptoms during quarantine in patients with dementia and their caregivers. METHODS: This is a sub-study of a multicenter nation-wide survey. A structured telephone interview was delivered to family caregivers of patients with diagnosis of Alzheimer disease (AD), dementia with Lewy bodies (DLB), frontotemporal dementia (FTD) and vascular dementia (VD), followed regularly at 87 Italian memory clinics. Variations in behavioral and psychological symptoms (BPSD) were collected after one month since quarantine declaration and associations with disease type, severity, gender and caregiver’s stress burden were analyzed. RESULTS: A total of 4913 caregivers participated in the survey. Increased BPSD was reported in 59.6% of patients as worsening of preexisting symptoms (51.9%) or as new onset (26%), and requested drug modifications in 27.6% of these cases. Irritability, apathy, agitation and anxiety were the most frequently reported worsening symptoms and sleep disorder and irritability the most frequent new symptoms. Profile of BPSD varied according to dementia type, disease severity and patients’ gender. Anxiety and depression were associated with a diagnosis of AD (OR 1.35, CI: 1.12-1.62), mild to moderate disease severity and female gender. DLB was significantly associated with a higher risk of worsening hallucinations (OR 5.29, CI 3.66-7.64) and sleep disorder (OR 1.69, CI 1.25-2.29), FTD with wandering (OR 1.62, CI 1.12-2.35) and change of appetite (OR 1.52, CI 1.03-2.25). Stress-related symptoms were experienced by two-thirds of caregivers and were associated with increased patients’ neuropsychiatric burden (p<0.0001). CONCLUSION: Quarantine induces a rapid increase of BPSD in approximately 60% of patients and stress-related symptoms in two-thirds of caregivers. Health services need to plan a post-pandemic strategy in order to address these emerging needs.